Investigation of luminescence excited by electrons from cold emission from a carbon nanotube cathode - Mroczkowski, Mateusz Patryk; Kalenik, Jerzy; Czerwosz, Elżbieta; Szmidt, Jan (Photonics Letters of Poland, 2010)
Modern light sources are expected to have low power consumption, high efficiency of light emission and to be ecological. This demand creates a need to develop new materials and technologies to fabricate light sources that will replace traditional, high power consuming light sources. Such new sources may use the phenomenon of luminescence excited by electrons, from cold emission. An investigation of cold electron emission from a carbon nanotube cathode was undertaken. As a part of this research, a nanostructural material built of carbon nanotubes was fabricated. A special test stand, including a four-section high voltage power supply, was assembled. The results will be used to anticipate the possibility of fabricating efficient light emitting devices based on such cathodes. Full Text: PDF References P. Hawken, A. Lovins, L. H. Lovins, Natural Capitalism (Back BayPress, Time Warner Book Group 2000) Wang, Q. Li, J. Xie, Z. Jin, J. Wang, Y. Li, K. Jiang, S. Fan,"Fabrication of Ultralong and Electrically Uniform Single-Walled Carbon Nanotubes on Clean Substrates", Nano Letters 9(9), 3137 (2009)[CrossRef] Y. Saito, S. Uemura,"Field emission from carbon nanotubes and its application to electron sources", Carbon 38, 169 (2000) [CrossRef] Y. Cheng, O. Zhou,"Electron field emission from carbon nanotubes", C. R. Physique 4, 1021 (2003)[CrossRef] G. A. J. Amaratunga, S. R. P. Silva,"Nitrogen containing hydrogenated amorphous carbon for thin-film field emission cathodes", Appl. Phys. Lett. 68, 2529 (1996)[CrossRef] A. V. Karabutov, V. D. Frolov, S. M. Pimenow,"Grain boundary field electron emission from CVD diamond films", V. I. Konov -Diamond and Rel. Mat. 8, 763 (1999)[CrossRef]